From Human Megakaryocytes to Platelets: Effects of Aspirin on High-Mobility Group Box 1/Receptor for Advanced Glycation End Products Axis - Mardente, Stefania; Mari, Emanuela; Massimi, Isabella; Tafani, Marco; Guerriero, Raffaella; Morsilli, Ornella; Pulcinelli, Fabio M.; Bianchi, Marco E.; Zicari, Alessandra (Frontiers in Immunology, 2018)
Platelets are the major source of HMGB1, a protein that is involved in sterile inflammation of blood vessels and thrombosis. Megakaryocytes synthesize HMGB1 and transfer both protein and mRNA into platelets and platelet-derived microvesicles. Quantities of free HMGB1 are found in supernatants of in vitro differentiated megakaryocytes and in a megakaryoblastic cell line (DAMI cells). Aspirin “in vivo” and “in vitro” not only reduces HMGB1 and RAGE expression on megakaryocytes and platelets, but also drives the movement of HMGB1 from megakaryocytes into platelets and platelet-derived microvesicles. These findings suggest that consumption of low doses of aspirin reduces the risk of atherosclerosis complications as well as reducing platelet aggregation by the inhibition of COX-1.